EFL TEACHER PROBLEMS IN CLASSROOM MANAGEMENT FACED IN ENGLISH CLASS - Dias Siti Munazar; Anne Ratna Suminar (Institut Pendidikan Indonesia Garut, 2021)
This study was aimed to find out the problems in managing classroom and strategies to cope these problems. To achieve the aforementioned purpose, qualitative approach embracing case study was employed. The data are gathered through interview as instrument. The data were analyzed inductively that was transcribed, categorized, analyzed, interpreted and concluded. As the result, problems in classroom management divided into three kinds, there are: noisy classes along with talkative students, not focus, and arrange the bench. And strategies to cope that problems in managing classroom, there are: punishment, build the relationship with student in learning processes, motivates the student to study, and organize the activities. Furthermore, this study suggests teachers be motivates and manage the time to be effective in managing the classroom.